2006
DOI: 10.1161/01.str.0000204037.26797.7f
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical Carotid Atherosclerosis in HIV-Infected Patients

Abstract: Background and Purpose-Whether or not combination antiretroviral therapy (CART) alone directly contributes to accelerating atherosclerosis in HIV-infected patients has not been studied in depth. This study aimed to ascertain the relationship between this therapy and subclinical carotid atherosclerosis according to cardiovascular risk. Methods-Sixty-eight HIV-infected patients with Յ1 cardiovascular risk factors and 64 with Ն2 risk factors completed the study protocol consisting of clinical, laboratory, and vas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(56 citation statements)
references
References 34 publications
4
50
1
1
Order By: Relevance
“…Although protease inhibitor exposure was not significantly associated with abnormal carotid ultrasound in our analysis, we found that longer duration of antiretroviral therapy was associated with an abnormal result. This finding was also found in an observational study by Jericho [25]. One possible explanation for why we were unable to detect a significant association with protease inhibitors exposure could be related to the short follow-up time in our study.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Although protease inhibitor exposure was not significantly associated with abnormal carotid ultrasound in our analysis, we found that longer duration of antiretroviral therapy was associated with an abnormal result. This finding was also found in an observational study by Jericho [25]. One possible explanation for why we were unable to detect a significant association with protease inhibitors exposure could be related to the short follow-up time in our study.…”
Section: Discussionsupporting
confidence: 81%
“…Our results are consistent with the literature and they support the notion that certain traditional risk factors for HIV disease progression are important contributors to atherosclerotic disease in the HIV population. Previous observational studies that investigated the relationship between traditional risk factors and carotid ultrasound surrogate markers in HIV patients have found similar results [23][24][25][26]. However, our analysis failed to demonstrate a significant association between carotid ultrasound abnormality and other traditional risk factors such as dyslipidemia, diabetes mellitus, hypertension and smoking.…”
Section: Discussionsupporting
confidence: 67%
“…Similar results were also reported by Hsue et al 92 and by Currier et al 93 in case-control studies suggesting that traditional risk factors may contribute to atherosclerosis in HIV-infected patients independently of PI exposure. Alonso-Villaverde et al reported that HIV-infected patients with subclinical atherosclerosis have higher circulating levels of monocyte chemoattractant protein-1 (MCP-1), especially of the allele MCP-1-2518G, compared to patients without atherosclerotic lesions, independently of HAART regimen 94 .Different results were reported by Maggi et al who observed a higher than expected prevalence of premature carotid lesions in PI-treated patients compared to PI-naive patients 95 .Similar results have been reported in a study by Jerico et al in 68 HIV-infected patients 96 . These authors conclude, stating that HAART should be considered a strong, independent predictor for the development of subclinical atherosclerosis in HIV-infected patients, regardless of known major cardiovascular risk factors and atherogenic metabolic abnormalities induced by this therapy 96 .…”
Section: Haart-associated Peripheral Vascular Diseasementioning
confidence: 55%
“…Similarly, longer exposure to HIV, even at low viral load levels, may allow for the direct effects of the virus to increase stroke risk. Second, combination antiretroviral therapy directly causes immune activation and metabolic and endothelial dysfunction that can accelerate atherosclerosis [9][10][11] and lead to symptomatic ischemic vascular events. 12,13 Third, hepatotoxicity is a known complication of combination antiretroviral drug treatment, 14 and in our multivariable analyses among factors independently linked to coexistent HIV infection with stroke hospitalization, mild liver disease had by far the strongest association.…”
Section: Resultsmentioning
confidence: 99%